Homeostatic Control in Grid-Connected Micro-Generation Power Systems: A Means to Adapt to Changing Scenarios While Preserving Energy Sustainability - Cordova-Gonzalez, F (2013)
We explore supervisory control strategies for the operation of grid-connected hybrid energy systems (HES) as complex adaptive systems. We do this not from a demand response management standpoint, like most of the literature does, but from a power generation and supply viewpoint, by means of homeostatic regulation and control with an aim for sustainable micro-generation systems for small-size communities. Homeostatic control (HC) is a term introduced by Fred C. Schweppe and his group of collaborators at MIT back in 1979 and early 1980s and stems from the highly visionary work done by them. We build on this concept and take a new approach, presenting our model and simulation results, which show clearly how HC and regulation of energy intake and expenditure by consumers, along with the presence of energy storage and compensatory mechanisms in the microgrid can provide much insight on how to make these systems more efficient, sustainable and resilient, particularly when integrated to the mains. Simulation provides a good fit to the data, and the response of the system to changing supply in different scenarios was characterized by its consistency and logical framework, supporting the model employed. © 2013 IEEE.